2005
DOI: 10.5713/ajas.2006.7
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Genetic Parameters for Reproductive Traits between First and Later Parities in Pig

Abstract: The objective of this study was to estimate genetic parameters between first and later parities as different traits in reproductive traits of pigs using multiple trait animal model procedures. Data related to reproductive traits from a total of 2,371 individuals maintained at a farm were taken from the pedigree file. Sires and dams were consisted of Duroc, Landrace, and Yorkshire breeds, respectively. The first and later parity records were considered as different traits. Traits included in analyses were total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 15 publications
7
26
3
Order By: Relevance
“…These results indicate that the sow's performance is unlikely to be repeated during the production period. This may be because physiological development of reproductive organs differs with parity (Oh et al, 2006). Thus, milk production in gilts may be 20% lower than in multiparous sows, as a consequence of lower feed intake and additional requirements of energy for tissue growth (Walker & Young, 1993).…”
Section: Resultsmentioning
confidence: 97%
“…These results indicate that the sow's performance is unlikely to be repeated during the production period. This may be because physiological development of reproductive organs differs with parity (Oh et al, 2006). Thus, milk production in gilts may be 20% lower than in multiparous sows, as a consequence of lower feed intake and additional requirements of energy for tissue growth (Walker & Young, 1993).…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies reported similar heritabilities of LSW and SVW (Damgaard et al, ; Lund et al, ; Putz et al, ; Roehe & Kennedy, ; Serenius at al., ; Su et al, ; Thekkoot, Kemp, Rothschild, Plastow, & Dekkers, ; Tomiyama, Kubo, Takagi, & Suzuki, ; Wolf et al, ; Zhang et al, ). Oh, Lee, and See () also estimated the heritability of LWW to be higher than that of LSW. Similarly, previous studies estimated the heritabilities of LWB and MWB to be higher than that of NBA (Damgaard et al, ; Hermesch, Luxford, & Graser, ; Ogawa et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In the population studied, it was more appropriate to use genetic parameters obtained by the multitrait model. Likewise, when estimating genetic parameters for reproductive traits among primiparous and multiparous WEI, Oh et al (2006) have reported that the genetic correlation estimates were not high enough to consider WEI observations of primiparous and multiparous to be a single trait.…”
Section: Resultsmentioning
confidence: 99%
“…The previous reproductive cycle may affect subsequent farrowing due to the effect of selection and permanent environment (Oh et al, 2006).…”
Section: Resultsmentioning
confidence: 99%